Anansi and the Talking Melon - Kimmel, Eric A.; Stevens, Janet (New York : Holiday House, 1994)
Tricky Anansi the spider plays a joke on Elephant and the other animals after Anansi gets stuck inside one of Elephant's melons, convincing everyone that Elephant has actually grown a talking melon.
Keywords: Anansi (Legendary character); Folklore -- Africa